Antecedents of trust and continuance intention in mobile payment platforms: The moderating effect of gender - Shao, Zhen; Zhang, Lin; Li, Xiaotong; Guo, Yue (Electronic commerce research and applications, 2019)
•Examine important trust building mechanisms in mobile pay platforms.•Mobility and customization as two dimensions of relative advantage of mobile payment.•Investigate the moderating effects of gender on various trust building mechanisms. Drawing upon trust and innovation diffusion theories, our study develops a model to examine trust building mechanisms in the third-party mobile payment platforms. In particular, we investigate whether there exist significant differences between female and male consumers regarding various trust building mechanisms in the context of mobile payment. An empirical survey was conducted and 740 valid questionnaires were collected from Alipay and Wechat pay users in China. The statistical analysis results indicate that security is the most significant antecedent of customers’ trust, followed by platform reputation, mobility and customization. Customers’ trust, in turn, is negatively associated with perceived risk and positively associated with continuance intention. Moreover, a multi-group analysis shows that the relative influences of trust building mechanisms are contingent upon gender. Specifically, mobility and reputation have stronger influences for male customers in building trust, while security and customization have more salient effects on trust for female customers.